2002
DOI: 10.1034/j.1600-0706.2002.980313.x
|View full text |Cite
|
Sign up to set email alerts
|

Grouping increases the ability of the social rodent, Octodon degus, to detect predators when using exposed microhabitats

Abstract: We examined the hypothesis that a main benefit of group‐living in the hystricognath rodent, Octodon degus (common degu), is to decrease individual risk of predation. During a first series of field observations, we contrasted group size of degus when using covered microhabitats with that of degus using exposed patches. During a second set of field observations, we assessed how distance to detection and to escape by degus varied with group size upon the approach of a potential human predator. Degus in exposed pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 46 publications
4
58
1
Order By: Relevance
“…located at higher altitude, in a more rigorous environment, exhibit a larger group size with more tolerance between individuals, and the greater number of marmots per group would reduce the loss of heat (Barash 1973(Barash , 1974Arnold 1988Arnold , 1990. Females of Octodon degus share a communal nest, which, among other things, allow them to improve thermoregulation (Ebensperger and Wallen 2002;Ebensperger et al 2004) because loss of body warmth is reduced by their crowding together in groups, and which becomes more efficient the larger the group size (Arnold 1988). The degree of behavioural specialization among individuals appears to increase with group size (Lacey 2000) and the total time and energy that animals allocate to specific activities, e.g.…”
Section: Introductionmentioning
confidence: 97%
“…located at higher altitude, in a more rigorous environment, exhibit a larger group size with more tolerance between individuals, and the greater number of marmots per group would reduce the loss of heat (Barash 1973(Barash , 1974Arnold 1988Arnold , 1990. Females of Octodon degus share a communal nest, which, among other things, allow them to improve thermoregulation (Ebensperger and Wallen 2002;Ebensperger et al 2004) because loss of body warmth is reduced by their crowding together in groups, and which becomes more efficient the larger the group size (Arnold 1988). The degree of behavioural specialization among individuals appears to increase with group size (Lacey 2000) and the total time and energy that animals allocate to specific activities, e.g.…”
Section: Introductionmentioning
confidence: 97%
“…Ebensperger and Wallem (2002) showed that group-living in Octodon degus (hystricognath) decreased individual risk of predation to human subject. Group-living in C. bishop as an anti-predator strategy should also be further investigated.…”
Section: Selection and Vulnerabilitymentioning
confidence: 99%
“…On the other hand, the opportunistic consumption or "avoidance" of this Echymyidae by the burrowing and barn owls, respectively, may be not only related to hearing capability, but also to differences in predator (145 g and 480 g, respectively) and prey (208.7 ± 65.2 g) sizes and difficulties in handling such large prey (Bueno and Motta-Junior 2008). As C. bishopi has a predominant quadrupedal locomotion, here considered the least efficient locomotion against predator attacks, it has to rely on other anti-predator strategies, such as hopping, tail loss (AAB, personal observation), digging, living underground (Ávila-Pires and Wutke 1981; Vieira 1997) and group-living (Ebensperger and Wallem 2002). Hopping, digging, jumping and ground activities are strategies used by other Echimyidae species (Manaf and Oliveira 2000) and by subterranean tuco-tucos (Ctenomys sp.)…”
Section: Selection and Vulnerabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The selective factors favoring communal nesting may act directly upon the adults that share a nest (e.g., increased predator detection; Macdonald 1981;Pilastro 1992;Ebensperger and Wallen 2002) or they may act upon the young reared in communal nests (e.g., increased protection from infanticide; Brown and Burt 2004;Manning et al 1995;Ebensperger 1998), thereby enhancing the fitness of parents that nest together. Because different selective factors may have distinct or even competing effects on the actions of individuals, it is important to understand how the various potential benefits of communal nesting interact to shape the behavior of animals that live and rear their young together.…”
Section: Introductionmentioning
confidence: 99%